A Learning Companion System for Distance Education in Computer Science - Faraco, Rafael A.; Rosatelli, Marta C.; Gauthier, Fernando A. O. (Anais do Workshop sobre Educação em Computação (WEI), 2004)
In this paper we present LeCo-EAD a Learning Companion System for distance education in computer science. LeCo-EAD includes multiple virtual learning companions that have different behaviours and are always available to interact with distant students. We show how a web-based distance course that adapts both its navigation support (links) and strategy (type of learning companion) to the student, can contribute to improve students’ motivation, reflection, and self-assessment skills. We report on the results of an experiment carried out with students and teachers of an undergraduate course on Object Oriented Programming in Java.